Homogeneity estimation morphometric model for particle distribution on example of SiC deposited on multilayer structure Fe/NiP - Komenda, T.; Korovytskyy, A.; Misyuk, S. (Физическая инженерия поверхности, 2012)
The theoretical justification of the distribution for particles/defects homogeneity estimation criterion
was done. The mathematical model was created on this basis and its object-oriented implementation
was realized. It is shown that the use of object-oriented programming allows getting a sufficient
clearness and simplicity of an object’s general mathematical model, displaying in it as the
object properties so and methods by which the model can operate. Adequacy of the proposed model
and research method was verified experimentally on samples of silicon carbide SiC deposited on
the multilayer structure of Fe/NiP. Здійснено теоретичне обґрунтування критерію для оцінки гомогенності розподілу часток/дефектів. На його основі створена математична модель і побудована її об’єктно-орієнтована реалізація. Показано, що використання об’єктно-орієнтованого програмування дозволяє з достатньою наочністю і простотою створити загальну математичну модель об’єкта, відобразивши
в ній як властивості самого об’єкта, так і методи, якими він може оперувати. Адекватність запропонованої моделі та методу дослідження була перевірена експериментально на зразках
карбіду кремнію SiC депонованого на багатошарову структуру Fe/NiP. Осуществлено теоретическое обоснование критерия для оценки гомогенности распределения
частиц/дефектов. На его основе создана математическая модель и построена ее объектно-ориентированная реализация. Показано, что использование объектно-ориентированного программирования разрешает с достаточной наглядностью и простотой создать общую математическую модель объекта, отобразив в ней как свойства самого объекта, так и методы, которыми он может оперировать. Адекватность предложенной модели и метода исследования
была проверена экспериментально на образцах карбида кремния SiC депонированного на
многослойную структуру Fe/NiP.